Population Biology Of The Greenback Grey Mullet, Chelon Subviridis (Valenciennes, 1836) In Merbok Estuary, Kedah - Mohd Rosli, Nor Aziella (2012)
The present research investigated population biology of the greenback grey mullet, C. subviridis in Merbok estuary for one year period from November 2010 to November 2011. This study is divided into four major components: (i) mullet fish identification using morphometric and meristic; (ii) length-weight relationship, length-length relationship and condition factor; (iii) reproductive biology; and (iv) growth, mortality and recruitment pattern. For the first component, 19 morphometric and 9 meristic characteristics were utilized. These characteristics were analyzed by univariate (analysis of variance) and multivariate analysis (principal component analysis and discriminant function analysis). Herein, the most important morphometric characteristics for classifying Mugilidae species were head width, snout length, body depth and distance from first dorsal fin to second dorsal fin. For meristic characteristics, the total number of soft rays at pectoral fin and total number of lateral scales was the most important meristic characteristics in the classification of Mugilidae species. The second component elucidated that the length-weight relationship (LWR) was in negative allometric pattern for males; W = 0.0128 L2.9347, females; W = 0.018 L2.8127 and combined sex; W = 0.0175 L2.823. Length-length relationship between total length (TL), standard length (SL) and fork length (FL) of C. subviridis were highly significant and highly correlated (r2 > 0.9579; p < 0.001). Besides, the mean condition factor of C. subviridis was 1.067 ± 0.092, had revealed that the Merbok estuary is in good ambience for survival and slightly favorable for C. subviridis.